PENGARUH MOTIVASI KUALITAS, MOTIVASI KARIR DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI - Jalila Ilmiha; Syafrizal Syafrizal (Universitas Islam Islam Sumatera Utara, 2018)
Global competition that has been started since 2016, the era of ASEAN Economic Community (AEC) requires a professional accountant, and hence, it requires additional education to have ability, competency and more readiness to compete in the labor world. Education for professional Accountant (PPAk) and Chartered Accountant (CA) is an advanced education to become professional and international accountant standard. So the government issued a law that regulates the education for professional accountant in 2014. Students who graduate PPAk and want to become a certified accountant must take the exam certification from Chartered Accountant (CA). Based on this conception the research was conducted to reveal the extent of interest of accounting students to join the program of PPAk and CA as a means to achieve professional level in the field of accountant. The study involved 200 students as sample and coming from different universities; the Islamic University of North Sumatera (UISU) and the Muhammadiyah University of North Sumatera (UMSU). The data were obtained from questionnaires which were spread up among the students through an accidental sampling approach in which the researcher obtained spontaneous data from the sample who met by accident. The collected data was analyzed through statistical approach, namely multiple linear regressions. The result of partial analysis, that is, motivation of quality and economic motivation have no effect on student interest to follow the program of PPAk and CA, while motivation of career was significantly positve influenced. While through simultant analysis, all the variables of motivation quality, career motivation and economic motivation all together influenced the students’ interest to take PPAk and CA program.